Optimization of Ethanol Production from Waste Bananas - MAZLAN, MUHAMMAD FARID (Universiti Teknologi PETRONAS, 2013)
Biofuel has been gaining momentum in terms of research and development. Since there are various factors such as recent rise in oil prices, support from government subsidies, and growing concern about global warming make biofuel the focal point of the public and researchers. The recent studies has come out with a new method for the production of ethanol using banana which is preferable compared to the old method of using other types of food-based feedstock such as corn, sugar cane, and potato. Various operating parameters available for the reaction also helps in providing significant effect on the products. Thus, different researches have to be done to further enhance and improve the production of ethanol from banana. Hence, this research study focuses on optimizing the ethanol production from banana using different parameters such as temperature and yeast concentration. The findings of this study can be used as a basis for comparison with other literature readings on the banana ethanol production having different operating conditions and parameters. Then, the effects of these different parameters are studied and optimized using Response Surface Methodology method. For the first part of the experiment, the study will focus on the different characteristics of banana especially on the growth rate effect on the weight of banana. While for the second part of the experiment, optimization of ethanol production from banana will be the main focus. This project dissertation serves to provide an introduction to the project, its background study, literature review, and also the detailed planning and methodology to carry out this research project to meet its objectives. It is expected that different parameters such as temperature and yeast concentration will affect the production of ethanol from banana which can further be optimized using the Response Surface Methodology method. The optimum yeast concentration and temperature for production of bioethanol from banana pulp is at 30°C and 0.10% w/v yeast concentration while for peel is at 40°C and 0.10% w/v yeast concentration, respectively.